Molecular Detections and Resistance Response of Six Rice Varieties to Tungroviruses from South Sulawesi - Saipul Abbas; Sri Sulandari; Sedyo Hartono; Y. Andi Trisyono (Universitas Gadjah Mada, 2020)
The suspected rice virus is found in the field, namely the tungrovirus which is transmitted by green leafhoppers (Nephotettix virescens). The study aimed to detect the tungrovirus molecularly and examine the resistance response of six rice varieties from the transmission of tungrovirus samples from South Sulawesi on a greenhouse scale. Based on the results of molecular detection with RTSV PCR of the double infected sample with DNA bands 1115 bp and RTBV of around 430 bp, Sidrap, and Maros samples were infected by 430 bp size RTBV, while Wajo sample was not detected by both viruses. The results of RTBV sequence analysis showed that the grouping of Sidrap was still one group with Maros and Pinrang samples and different from the group of samples from Malaysia, Thailand, and Philippines. While the grouping of RTSV shows that Pinrang samples are still one group with samples from Bali, Subang, and different from those of the Philippines, India, and Malaysia. The results of transmission in the greenhouse on six rice varieties (TN1, Ciherang, Mekongga, Tukad Unda, Inpari 36, Inpari 37) showed different plant resistance responses such as susceptible, moderately resistant, and resistant reactions based on the amount of disease intensity caused. Varieties that are classified as susceptible are TN1 and Ciherang varieties, moderately resistant, namely Mekongga and Tukad Unda varieties, and resistant varieties namely Inpari 36 and Inpari 37 varieties.